1991
DOI: 10.1017/s1041610291000480
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Factor Structure of the Geriatric Depression Scale

Abstract: The Geriatric Depression Scale (GDS) is commonly used to measure depression in the elderly. However, there have been no reports of the underlyingstructureoftheGDS. Tothisend,theGDS was administered to 326 community-dwelling elderly subjects, and the data were subjected to a factor analysis. A five-factor solution was selected and, after a varimax rotation, the factors that emerged could be described as: (1) sad mood, (2) lack of energy, (3) positive mood, (4) agitation, and (5) social withdrawal. This solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
206
1
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(216 citation statements)
references
References 14 publications
2
206
1
5
Order By: Relevance
“…MMSE scores range from 0 to 30, with higher scores indicating greater cognitive function. Depression was evaluated using the Short Form-15 Geriatric Depression Scale (GDS) (Sheikh et al 1991). GDS scores range from 0 to 15, with higher scores indicating severe depression.…”
Section: Secondary Outcomementioning
confidence: 99%
“…MMSE scores range from 0 to 30, with higher scores indicating greater cognitive function. Depression was evaluated using the Short Form-15 Geriatric Depression Scale (GDS) (Sheikh et al 1991). GDS scores range from 0 to 15, with higher scores indicating severe depression.…”
Section: Secondary Outcomementioning
confidence: 99%
“…The final covariates included age, sex, years of education, depressive symptoms, apolipoprotein (APOE) genotype, cardiovascular disease risk (measured by the modified Framingham Risk Score), history of cancer, incidence of CVA, AMI, angina, serum levels of tumor necrosis factor-a (TNF-a), CRP, interleukin-6 (IL-6), and interleukin-12 (IL-12). Depressive symptoms were assessed by the 15-item Geriatric Depression Scale (Sheikh et al, 1991), which has been shown to be valid and to have excellent test-retest reliability (Sheikh et al, 1991). MIC-1/GDF15 has been shown to be associated with tumor grade, cancer stage and prognosis, and systemic inflammation (Bauskin et al, 2006).…”
Section: Covariatesmentioning
confidence: 99%
“…Normal and IFG states were defined using the American Diabetes Association criteria: normal ≤5.5 mmol/L, IFG defined by glucose between 5.6 and 6.9 mmol/L. Depressive symptoms were assessed by the 15-item Geriatric Depression Scale (GDS; Sheikh and Yesavage 1986), which has been shown to be valid and have excellent test re-test reliability (Sheikh et al 1991). The continuous GDS was included as a covariate.…”
Section: Covariatesmentioning
confidence: 99%